European Union's pursuit of resilience in the Eastern Neighbourhood - Loredana Simionov (CES Working Papers, 2020)
Over the past decades, the EU has faced a variety of challenges and shocks that have shaken the Union up to its very core, with crisis emerging both internally and externally (i.e. the sovereign debt crisis, terrorist attacks, refugees' crisis, Ukraine crisis, Brexit, pandemic crisis). Within this context, it is not surprising that EU's resilience has become the ultimate goal across various fields and sectors. Accordingly, resilience has found its way into EU's foreign affairs and agenda particularly after the Ukraine crisis, which has emphasised the Union's inability to predict and manage crisis emerging in its near abroad. In this context, the aim of the paper is to analyse EU's understanding of resilience beyond its borders, as a pragmatic turn, away from its transformative incentives. In practice, the paper will focus on the Eastern Partnership (EaP) region, where the EU has put considerable efforts to shape a coherent approach to resilience. The argument is that, despite the EU's efforts and intensions, the pursuit of resilience abroad entails a series of contradictions and frictions between the EU's own resilience and that of the EaP countries, revolving around the dichotomy between interests and values.
Keywords: 330; resilience; interests; values; European Union; Eastern Neighbourhood